Developing and Validating the Research Skills Metacognitive Questionnaire: A Comprehensive Exploration of Instrument Design and Validation - Sagita, Sylva; Rahmat, Adi; Priyandoko, Didik; Sriyati, Siti (Migration Letters, 2023)
The primary aim of the current paper is to illuminate the intricate process of developing the Research Skills Metacognitive Questionnaire (RSMQ), a specialized instrument crafted to assess students’ metacognitive engagement in research skill development. The primary objective is to illuminate the pivotal steps undertaken in the initial validation of the RSMQ, leveraging statistical tests and employing the Rasch model. The culmination of this process yields a finalized survey instrument featuring 62 questionnaire items. Notably, the instrument demonstrates commendable item and person reliability, with 58 items fitting well within theRasch fit item criteria. This endeavour contributes to advancing assessment tools tailored to gauge metacognitive aspects in the dynamic context of research skill development among students.